Acute mental health service use is increased in rheumatoid arthritis and ankylosing spondylitis: a population-based cohort study. (June 2020) - Kuriya, Bindee; Tia, Vivian; Luo, Jin; Widdifield, Jessica; Vigod, Simone; Haroon, Nigil
Background: Rheumatoid arthritis (RA) and ankylosing spondylitis (AS) are associated with mental illness. Whether acute mental health (MH) service utilization (i.e. emergency visits or hospitalizations) is increased in RA or AS is not known. Methods: Two population-based cohorts were created where individuals with RA ( n = 53, 240) or AS ( n = 13, 964) were each matched by age, sex, and year to unaffected comparators (2002–2016). Incidence rates per 1000 person-years (PY) were calculated for a first MH emergency department (ED) presentation or MH hospitalization. Hazard ratios (HR) and 95% confidence intervals (CI) were calculated, adjusting for demographic, clinical, and health service use variables. Results: Individuals with RA had higher rates of ED visits [6.59/1000 person-years (PY) versus 4.39/1000 PY in comparators] and hospitalizations for MH (3.11/1000 PY versus 1.80/1000 PY in comparators). Higher rates of ED visits (7.92/1000 PY versus 5.62/1000 PY in comparators) and hospitalizations (3.03/1000 PY versus 1.94/1000 PY in comparators) were also observed in AS. Overall, RA was associated with a 34% increased risk for MH hospitalization (HR 1.34, 95% CI 1.22–1.47) and AS was associated with a 36% increased risk of hospitalization (HR 1.36, 95% CI 1.12–1.63). The risk of ED presentation was attenuated, but remained significant, after adjustment in both RA (HR 1.08, 95% CI 1.01–1.15) and AS (HR 1.14, 95% CI 1.02–1.28). Conclusions: RA and AS are both independently associated with a higher rate and risk of acute ED presentations and hospitalizations for mental health conditions. These findings underscore the need for routine evaluation of MH as part of the management of chronic inflammatory arthritis. Additional research is needed to identify the underlying individual characteristics, as well as system-level variation, which may explain these differences, and to help plan interventions to make MH service use more responsive to the needs of individuals living with RA and AS.